Improvements on high-temperature stability, rheology, and stiffness of asphalt binder modified with waste crayfish shell powder. (10th August 2020) - Lv, Songtao; Xia, Chengdong; Yang, Qing; Guo, Shuaicheng; You, Lingyun; Guo, Yanpeng; Zheng, Jianlong
Abstract: The quickly accumulated crayfish shell waste in China has led to severe environmental issues and recycling pressure. This study aims to build an efficient protocol by utilizing waste crayfish shell powder in the production of high-performance and sustainable asphalt binder. The asphalt binder modified with different contents of crayfish shell powder (5%, 10% and 20% mass ratio to control asphalt, respectively) were first prepared at the temperature of 140 o C–150 °C. Then the softening point and the penetration of the prepared samples were implemented to compare the stiffness difference between the modified and original asphalt binder. The results indicated that the added shell powder increased the softening point and decreased the penetration of the control asphalt. Furthermore, the high-temperature stability of the asphalt binder was examined by the dynamic shear rheometer (DSR) tests. The DSR results revealed that adding shell powder could enhance the rutting resistance of the asphalt binder by decreasing the phase angle δ, increasing the dynamic shear modulus |G∗| and finally enhancing the rutting factor |G∗|/sinδ. After that, to compare the creep performance between the control and modified asphalt binder, the multiple stress creep recovery (MSCR) tests were employed. The results of the MSCR test showed that at the same temperature, the percent recovery was higher while the non-recoverable creep compliance Jnr of modified asphalt was lower than those of the control binder. These results indicated that the added crayfish shell powder could increase the stiffness, improve the high-temperature stability and creep resistance of the asphalt binder. Finally, fourier transform infrared spectroscopy (FT-IR) test results implied that the added CS would not affect the chemical structure of the asphalt binder, and the modification was mainly a physical process. The novelty and limitation of this study have also been detailedly explained in the discussion part. The test results could provide a reference for the engineering application of the crayfish shell powder modified asphalt material and lead to both a cleaner and greener product.